2011
DOI: 10.1590/s0103-21002011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes portadores de doença inflamatória intestinal

Abstract: Objectives:To assess the quality of life (QV) in patients with inflammatory bowel disease (DII), and relate it to demographic data and morbidity. Methods: Cross-sectional study with 103 patients with DII, registered in the high cost pharmacy of Cuiabá -Mato Grosso, who responded to the Standard Medical Record, the general QV questionnaire SF-36 and the specific IBDQ. Results: Among 103 patients with DII, 62 had ulcerative colitis and 41 had Crohn's disease; 62% were women; 69.9% were married; 48.5% were of mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
14
2
29

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 21 publications
7
14
2
29
Order By: Relevance
“…Although tobacco consumption has been considered as one of the most important environ-mental factors in the pathogenesis of IBD, little is still known about the molecular and cellular mechanisms triggered in the intestine, which may lead to the development of CD or the prevention of UC (Pereira, 2014). In this study, the majority of participants reported never having smoked (65.80%) and not drinking alcohol (71.10%), which is in line with the studies by Coelho (2010) and Souza et al (2011) with 54 smokers (93.10%) versus four non-smokers (6.90%) and 51 smokers (49.50%) versus 52 participants non-smokers (50.50%), respectively, with no significant difference between them. With regard to the most prevalent type of IBD, the most common type in this study was CD (50.00%), followed by UC (26.30%) and undetermined IBD (23.70%), which is in line with several studies, namely those by Ramos et al (2015) and Magalhães et al (2015) which had a higher number of people with CD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although tobacco consumption has been considered as one of the most important environ-mental factors in the pathogenesis of IBD, little is still known about the molecular and cellular mechanisms triggered in the intestine, which may lead to the development of CD or the prevention of UC (Pereira, 2014). In this study, the majority of participants reported never having smoked (65.80%) and not drinking alcohol (71.10%), which is in line with the studies by Coelho (2010) and Souza et al (2011) with 54 smokers (93.10%) versus four non-smokers (6.90%) and 51 smokers (49.50%) versus 52 participants non-smokers (50.50%), respectively, with no significant difference between them. With regard to the most prevalent type of IBD, the most common type in this study was CD (50.00%), followed by UC (26.30%) and undetermined IBD (23.70%), which is in line with several studies, namely those by Ramos et al (2015) and Magalhães et al (2015) which had a higher number of people with CD.…”
Section: Discussionsupporting
confidence: 92%
“…As regards the family relationships, most of the participants in this study are married (65.80%), which is in line with the study by Souza et al (2011), with a mean of 69.90% of married participants, but in disagreement with the results obtained by Neubauer, Arlukiewicz, and Paradowski (2009), who found that most of the patients with CD live alone and do not start a family. As for the education level, most of the participants in this study had completed the 12 th grade (28.90%) and higher education (28.90%), which is not in line with the results obtained by Coelho (2010), who found a higher percentage of participants with the 9 th grade (56.90%).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The demographic and socioeconomic findings were in agreement with data reported in the literature showing a greater frequency of IBD among women, a bimodal age distribution occurring between 20 and 40 years, as well as greater frequencies among residents of urban areas, economically active individuals and those from lower economic classes (10,35,39) . In a review of the literature, Loftus (22) suggests that the predominance of IBD in the female sex is due to the role of hormonal factors in the development of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Another study addressing patients in the active phase of an intestinal inflammatory disease indicated QOL is compromised. Physical aspects, vitality, and emotional aspects are the domains mostly affected by the symptoms presented by patients, which can greatly impact their behavior in emotional, physical and social terms (21) . Another study addressing patients with extensive and metastatic colorectal cancer observed deterioration in the patients' physical functioning (22) .…”
mentioning
confidence: 99%